Hubungan Kualitas Kehidupan Kerja Dengan Produktivitas Kerja Perawat Di RSUD Latemmamala Kabupaten Soppeng - Guntur, Rahmatika; Andi Sani; Nurgahayu (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Nurses' work productivity is a key element in ensuring the quality of healthcare services. This study, conducted at Latemmamala Regional General Hospital, Soppeng Regency, aimed to analyze the relationship between the quality of work life and nurses' work productivity. The research method used was a quantitative approach with a cross-sectional design. A sample of 150 non-ASN nurses was selected using a stratified random sampling method. Data were collected through questionnaires and analyzed using the chi-square test. The results showed that work environment safety (p=0.001) and career development (p=0.000) had a significant relationship with nurses' work productivity. Meanwhile, compensation (p=0.290), welfare (p=0.552), and communication (p=0.008) variables did not show a significant relationship. It can be concluded that quality of work life, especially aspects of work safety and career development, influence nurses' work productivity. Therefore, hospital management is advised to increase efforts in these two aspects while still paying attention to other factors to create an optimal work environment. These recommendations provide clear guidance for the next steps in improving nurses' work productivity.